Innovation on Health Care with Thai Traditional Medicine and Alternative Medicine in Healthcare System - Wattana, Sanchai (Journal of Health Science of Thailand, 2018)
The study on the procession of lifestyle clinics in Chon Buri was aimed at assessing the procession’s results by using systematic theory according to CIPP Model. The study focused on performers and counselors in lifestyle clinics in the fourteen hospitals that were contract partners of health assurance. They gathered information from group conversation and studied document records reporting all procession from November 2005 on. The received information had been checked for precision and completion before its context was analyzed. The results revealed that general clinics had the structure of administration in the form of committee-performers most of whom were vocational nurses working in multi professional way. Most lifestyle clinics furthered, with continuation, the procession of special clinics for chronic diseases namely diabetes. Some of them furthered the procession continually according to policies such as parental school policy. All the procession was perpetuated with the help of voluntary participants of the good health clinics. The steps of the procession consisted of program explanation, process in activities to adjusting behaviors, and assessment. Moreover, the procession was also run by activity groups and the period of procession varied in various places. The results of procession run by lifestyle clinics offered more social-mental service. The staffs who provides the services were proud of helping patients to adjust health behaviours.